Climate Policy and the Intertemporal Supply of Fossil Resources - Christian Beermann (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2015)
This thesis was written by Christian Beermann while he was a research assistant at the Center for Economic Studies (CES) at the University of Munich. It was completed in December 2014 and accepted as a doctoral thesis by the Department of Economics at the University of Munich in May 2015. The thesis analyses the intertemporal supply reaction of the fossil resource supply side to demand-reducing climate policies while explicitly taking into account the global warming problem. The interaction between a climate coalition that can either be global or incomplete, comprising only a subset of the world's countries in the latter case, and a representative competitive resource supplier is analysed in a Stackelberg differential game in which the coalition leads.
Keywords: H23; O13; Q32; Q38; Q54; 330; Klimawandel; Klimaschutz; Internationale Klimapolitik; Fossile Energie; Ressourcenökonomik; Intertemporale Allokation; Ökosteuer; Umweltpolitik; Umweltökonomik; Theorie; Klimaschutz; Klimapolitik; Fossile Energie; Ressourcenökonomik; Intertemporale Allokation; Umweltpolitik; Umweltökonomik; Theorie